Front Cover Translator Visibility and Language of Publication in the Context of Fiction Published in Canada - Butt, Jeffrey (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2020)
The names of translators often, perhaps even usually, do not appear on the front covers of books they have translated. When their names do appear on front covers, they tend to be presented as inconspicuously as possible. Despite the recent social or ideological turn of Translation Studies, which regards translators as performative agents and affords more attention to the environment and conditions, including political, linguistic and cultural, in which they work, the issue of translators’ paratextual – and, more specifically, front cover – visibility has not garnered significant attention. The aim of this dissertation is to determine whether, in Canada, it is English-language or French-language publishers of fiction in translation that are more likely to paratextually recognize the contributions of translators. Such recognition is defined as the frequency of front cover translator mentions and their size relative to total front cover surface area and that of other front cover paratextual features, such as title and author. This dissertation will offer a summary of issues surrounding translator visibility, including some key writings on translators’ paratextual visibility, in order to make a case for conferring authorial status upon translators, which is necessary to justify this inquiry into their front cover presence. Dozens of Canadian publishers were asked to participate in this study, the findings of which are based on four English-language publishers and two French-language publishers which, collectively, published 32 translated works of fiction (21 English and 11 French) in 2018 and 2019.
Keywords: Literary Translation